Design, synthesis and evaluation of MCH receptor 1 antagonists—Part I: Optimization of HTS hits towards an in vivo efficacious tool compound BI 414. Issue 16 (15th August 2015) - Müller, Stephan G.; Heckel, Armin; Kley, Jörg T.; Lehmann, Thorsten; Lustenberger, Philipp; Oost, Thorsten; Roth, Gerald J.; Rudolf, Klaus; Arndt, Kirsten; Lenter, Martin; Lotz, Ralf R.H.; Maier, Gerd-Michael; et al.
Graphical abstract: Abstract: Despite recent approvals of anti-obesity drugs there is still a high therapeutic need for alternative options with higher efficacy in humans. As part of our MCH-R1 antagonist program for the treatment of obesity, a series of biphenylacetamide HTS hits was evaluated. Several issues of the initial lead structures had to be resolved, such as potency, selectivity over related GPCRs and P-gp efflux limiting brain exposure in this series. We could demonstrate that all parameters can be significantly improved by structural modifications resulting in BI 414 as a potent and orally available MCH-R1 antagonist tool compound with acceptable in vivo efficacy in an animal model of obesity.